Efeito de metais de transição sobre a polarização espontânea na estrutura cristalina de nanopós da família tungstênio bronze - Lima, Alan Rogério Ferreira (2011)
This work aimed the study of the effect of transition metals (Ni, Fe, Co) on the spontaneous polarization of the ferroelectric oxides of tetragonal tungsten bronze (TTB)-type structure of potassium strontium niobate (KSr2Nb5O15) and of the KSr2(FeNb4)O15-d, KSr2(NiNb4)O15-d and KSr2(CoNb4)O15-d solid solutions. All systems investigated were prepared by mechanical mixture of oxide/carbonates by high-energy ball milling. The calcination temperature was performed to obtain nanoparticles and the nanostructured particles were evaluated. The evolution of mass loss, chemical bonds, crystalline structure and the electrical behavior were evaluated using the thermal analysis (thermogravimetric Analysis (TGA) and Differential Scanning Calorimeter (DSC), infrared absorption spectroscopy (FTIR), X-ray diffraction (XRD) and impedance spectroscopy, respectively. From the impedance spectroscopy technique were studied the dielectric properties of the nanoparticles and the dielectric permittivity of the KSr2Nb5O15, KSr2(FeNb4)O15-d, KSr2(NiNb4)O15-d and KSr2(CoNb4)O15-d systems was determined. The highest permittivity value was obtained for KSr2(FeNb4)O15-d. The determination of crystallographic parameters of nanopowders was performed using the Rietveld method. From the crystallographic parameters was simulated the crystalline structure and determined the spontaneous polarization for KSr2Nb5O15, KSr2(FeNb4)O15-d, KSr2(NiNb4)O15-d and KSr2(CoNb4)O15-d systems based on the atomic displacement (Dz) of Nb (niobium) atom, in the z plane, from the central position of the [NbO6] octahedron. The variation of spontaneous polarization of the nanoparticles with the addition of transition metals in the KSr2Nb5O15 host structure confirmed the existence of ferroelectricity in the systems investigated.